2018
DOI: 10.1111/apa.14598
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of screening for coeliac disease in children with juvenile idiopathic arthritis

Abstract: Aim To study the prevalence of coeliac disease (CD) in children with Juvenile idiopathic arthritis (JIA), by screening a population‐based cohort of children with JIA using autoantibodies against tissue transglutaminase (anti‐TG2). Methods All children diagnosed with JIA in three Swedish counties, with disease onset between 2007 and 2014, were included prospectively. Serum levels of IgA anti‐TG2 antibodies, IgG anti‐TG2 antibodies, and total IgA were analysed. Children with positive levels of IgA anti‐TG2 antib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 26 publications
1
12
1
Order By: Relevance
“…In line with previous data [ 9 , 10 ], at the time of CD diagnosis, most patients were asymptomatic, thus underlining the importance of systematic screening for CD among JIA patients even in the absence of suggestive symptoms.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…In line with previous data [ 9 , 10 ], at the time of CD diagnosis, most patients were asymptomatic, thus underlining the importance of systematic screening for CD among JIA patients even in the absence of suggestive symptoms.…”
Section: Discussionsupporting
confidence: 89%
“…In contrast to their study, reporting a 0,7% CD prevalence among JIA patients, but in line with other reports [ 2 – 4 , 8 , 9 ], we found a prevalence of 2,4%, more than twice higher than that of CD in the general population in Italy [ 14 ], as well as in Europe [ 15 ]. Similarly, Oman and colleagues found a CD prevalence of 2,8% among 216 Swedish JIA patients [ 10 ]. In contrast to what observed in northern European countries [ 5 , 10 ], a small Brazilian study found 4 in 45 (8,8%) JIA patients to have positive CD-specific serology, however no biopsy was performed [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Also in this issue, Öman et al. report that there was no increased occurrence of coeliac disease in children with juvenile idiopathic arthritis when they were compared to healthy children. Meanwhile, Nurminen et al.…”
Section: Dietitian Visits Provided Safe and Cost‐effective Follow‐up mentioning
confidence: 97%
“…Inflammatory bowel disease, including Crohn disease, ulcerative colitis and undifferentiated colitis, occurs in 5–10% of patients affected by ERA, more frequent in males, at the onset or during disease course ( 11 ). In addition, celiac disease occurs in 1–8% of patients with ERA ( 12 ), while SAPHO syndrome is an even less frequent complication characterized by axial involvement along with enthesitis and peripheral arthritis and typical cutaneous findings ( 13 , 14 ).…”
Section: Introductionmentioning
confidence: 99%